Identification of spectrally enhanced Polish vowels - OZIMEK, Edward (Archives of Acoustics, 2007)
The role of spectral enhancement in identification of Polish vowels is investigated in this study. Identification scores of natural (unprocessed) vowels (Experiment 1) and spectrally enhanced vowels (Experiment 2) were measured for normal-hearing subjects (NHS) and for subjects with hearing impairment of cochlear origin (HIS). The NHS group demonstrated almost 100% vowel-identification scores for natural vowels. Instead, for the HIS group, an overall average identification scores were 85% for natural vowels, 96% for spectrally enhanced vowels. It has been shown that the spectral enhancement applied has improved the average identification score for subjects with sensorineural hearing losses. However, the degree of improvement clearly depended on the subjects, the type of vowel, and the talker.